Sex and Feeding Status Differently Affect Natural Reward Seeking Behavior in Olfactory Bulbectomized Rats - Ruda-Kucerova, Jana; Zanda, Mary Tresa; Amchova, Petra; Fratta, Walter; Fattore, Liana (Frontiers in Behavioral Neuroscience, 2018)
Substance abuse and depression are common psychiatric disorders with a high rate of comorbidity. Both conditions affect differently men and women and preclinical research has showed many sex differences in drug addiction and depression. The most common approach for modeling depression-addiction comorbidity is the combination of the intravenous drug self-administration and the olfactory bulbectomy (OBX) models in rats. Such a combination has revealed enhanced drug-taking and drug-seeking behaviors in OBX rats, but no study has investigated so far potential sex differences in operant responding and motivation for natural reinforcers in OBX rats. This study investigated for the first time operant self-administration of palatable food pellets in male and female OBX rats under different feeding status, i.e. ad libitum vs restricted food, and schedules of reinforcement, i.e. a continuous ratio schedule (FR1) vs a complex (FR5(x)) second order schedule of reinforcement. In the FR1 experiment, OBX rats of both sexes exhibited lower operant responding and intake of palatable food pellets than sham-operated controls, with food restriction leading to increased operant responding in both OBX and SHAM groups. Female rats showed higher responding than males but this effect was abolished by the OBX lesion. Similarly, in the (FR5(x)) second order schedule of reinforcement both male and female OBX rats showed lower responding and food intake, with SHAM and OBX females showing higher operant responding than corresponding male groups. Overall, our study findings showed that (i) responding for food was lower in OBX than in SHAM rats under both FR1 and (FR5(x)) schedules of reinforcement, (ii) sex and food restriction affect operant responding for palatable food, (iii) the suppressing effect of OBX lesion on food intake was consistently present in both sexes and represents the most robust factor in the analysis. This may represent anhedonia which is associated with depressive-like phenotype and palatable food self-administration may serve as a robust behavioral index of anhedonia in the OBX model.